Determinan Perilaku Pemberian ASI Eksklusif di Wilayah Kerja Puskesmas Alai Ilir Kabupaten Tebo - Lia Nurdin; Budi Aswin; Ihtiar Yuni Sasmita (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2022)
The coverage of exclusive breastfeeding is still low in various regions, one of which is in Tebo Regency. Research objective: This study aims to analyze the determinants that affect the behavior of exclusive breastfeeding in infants aged 7-12 months in the Alai Ilir Health Center Work Area, Tebo Regency. Research methods: This study used a cross sectional design. The population of all mothers who have babies 7-12 months is 188 and a sample of 94 respondents with the sampling technique of proportionate stratified random sampling. Data were collected through interviews and analyzed using chi square. The results showed that 59.6% of respondents did exclusive breastfeeding. Most of the respondents are aged 20-35 years (94.7%), highly educated (89.4%), not working (58.5%), good knowledge (78.7%), husband is supportive (52.1%), health workers are supportive (55.3%), and their breastfeeding is smooth (63.8%). There was a relationship between mother's knowledge (PR = 2.158; 95% CI:1.395-3.339 husband's support (PR= 1.867; 95% CI:1.109-3.141), (PR=2.834; 95% CI: 1.670-4.808) and the smoothness of breastfeeding (PR=2.180; 95% CI:1.347-3.528) with exclusive breastfeeding behavior. There is no relationship between maternal age, mother's education, mother's occupation and support from health workers with exclusive breastfeeding behavior. It is necessary to increase mother's knowledge about matters related with increasing and maintaining the smoothness of breast mil.